La rappresentazione di un potere: Il vescovo di Anagni Pietro da Salerno († 1105) - Mengarelli, Cristiano (Incontri. Rivista europea di studi italiani, 2013)
Representation of Power The Bishop of Anagni, Pietro da Salerno († 1105) In the history of Anagni, Bishop Pietro da Salerno was fundamental in guaranteeing that the city played an important political role throughout the Middle Ages. His work as a spiritual guide, his interventions on the urban layout and the way in which this combination of factors was reflected in the historical memories which formed around the figure of the bishop help to consolidate its historical tradition. Pietro da Salerno used his office of bishop in the certainty that he was acting on behalf of an established power, to be consolidated in his own time and offered as a stable and secure legacy for the future. The representation of this power took the form of an action program, centered around the urban renewal of an entire city district with the aim of creating an architectural ‘macro-palimpsest’ serving as a political manifesto based on the recovery, through continuity, of the historical, hagiographic and material legacy which defined and recalled, in a simple but immediate form, the power of the bishops over the city of Anagni. We are thus dealing with a legitimization of power through the representation of historical events and allusions, expressed through the stylistic features of the contemporary cultural tradition.